ETV2/ER71, the key factor leading the paths to vascular regeneration and angiogenic reprogramming - Tae Min Kim; Ra Ham Lee; Min Seong Kim; Chloe A. Lewis; Changwon Park (Stem Cell Research & Therapy, 2023)
Abstract Extensive efforts have been made to achieve vascular regeneration accompanying tissue repair for treating vascular dysfunction-associated diseases. Recent advancements in stem cell biology and cell reprogramming have opened unforeseen opportunities to promote angiogenesis in vivo and generate autologous endothelial cells (ECs) for clinical use. We have, for the first time, identified a unique endothelial-specific transcription factor, ETV2/ER71, and revealed its essential role in regulating endothelial cell generation and function, along with vascular regeneration and tissue repair. Furthermore, we and other groups have demonstrated its ability to directly reprogram terminally differentiated non-ECs into functional ECs, proposing ETV2/ER71 as an effective therapeutic target for vascular diseases. In this review, we discuss the up-to-date status of studies on ETV2/ER71, spanning from its molecular mechanism to vasculo-angiogenic role and direct cell reprogramming toward ECs. Furthermore, we discuss future directions to deploy the clinical potential of ETV2/ER71 as a novel and potent target for vascular disorders such as cardiovascular disease, neurovascular impairment and cancer.